Knowledge and attitude towards ethical cadaver dissection among medical and health sciences students, 1997-2020: A systematic review and meta-analysis - Yoseph Merkeb Alamneh (Elsevier, 2021)
Abstracts: Background: Human cadaveric dissection has been utilized as the major teaching method for human anatomy since ancient Greece in the 3rd century Before Christ (BC). Globally, despite the advancement of modern technology and changing teaching methods, human cadaveric dissection has remained the major platform for teaching gross anatomy to medical and health science students. Cadaveric dissection provides for a comprehensive understanding of the three-dimensional relationships that are so important in comprehending human anatomy for clinical practice. Though many scattered studies have been published so far, worldwide research that represents a global level of knowledge and attitude towards ethical cadaver dissection is lacking, and their results have been contradictory and inconclusive. Therefore, this systematic review and meta-analysis aimed to estimate the pooled prevalence of knowledge and attitude towards ethical cadaver dissection among medical and health sciences students. Methods: This review was reported according to Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocol (PRISMA-P) guidelines. International databases like PubMed, SCOPUS, Google Scholar, and Science Direct were systematically searched on knowledge and attitude towards ethical cadaver dissection among medical and health sciences students from 1997 to 2020. To analyze the data, STATA™ Version 14.1 was used. To determine heterogeneity and publication bias, the Cochrane Q and I2 test, and both Egger's and Begger's tests were used, respectively. The pooled prevalence and odds ratios were estimated with confidence intervals of 95%. Finally, a random-effects meta-analysis model was calculated to estimate the pooled prevalence of knowledge and attitude towards ethical cadaver dissection. Results: We screened a total of 460 articles. Of these, 15 studies were included in the final systematic review and meta-analysis. The pooled prevalence of knowledge and attitude towards ethical cadaver dissection among medical and health sciences students were 66.78% (95% CI: 45.62, 87.94; I2 = 98.6%, p-value <0.001) and 67.49% (95% CI: 56.07, 78.91; I2 = 98.7%, p-value <0.001) respectively. The subgroup analysis was conducted on 3 Ethiopian studies (59.87% [95% CI: 15.33, 104.41]), 5 researches in India (73.24% [95% CI: 56.07, 90.42]), 5 on the African continent (64.4% [95% CI: 37.85, 90.95]) and 9 in Asia (68.34% [95% 31 CI: 55.35, 81.33]). Conclusion: Overall, two-thirds of the participants had adequate knowledge and a favorable attitude towards ethical cadaver dissection, whereas one-third had inadequate knowledge and an unfavorable attitude. The dissection room should be environmentally friendly and conducive to overcome the obstacles that students face when practicing cadaveric dissection. Furthermore, instructors must psychologically and emotionally prepare students before they enter the dissecting room so that they may become more active participants in cadaver dissection, improving anatomical knowledge and future surgical skill. Moreover, medical curriculum developers and policymakers should understand the implications of dissection in clinical practice. Further research is also needed to see if factors impacting knowledge and attitudes towards ethical cadaver dissection are consistently distributed worldwide, nationally, and regionally, so that appropriate interventional strategy may be implemented.